Information System Design Based E-Commerce in Food Marketing - ., Winarto; Kusuma, Yanda Bara; Syarifudin, Muhammad (Asian Journal of Social Sciences and Management Studies, 2019)
Information system based e-commerce is the most important method in food marketing in term of promotion costs and automatic data without human error. The system serves consumers by providing an easy and effective transaction.Information system based e-commerce has proven to satisfyconsumer needs. Therefore, this research aims to design a website-based information system marketing which is better than manual system applied in CV.Sari Kelapa Group. CV. Sari Kelapa Group is an individual company that develops into a large company and was founded in 1967s engaged in the production of Gresik food producers. Pudak is the first product of the company. Promotion at CV. Sari Kelapa Group, It is a fact that unavailability of appropriate promotional media in promoting the products are obvious. Furthermore, the approach uses prototype research and descriptive qualitative by giving interview to the subject. The results show that the website is able to overcome the short comings of the manual system applied by CV.Sari Kelapa Group and recommend a complete feature of online chat.